Factors Influencing Tourists’ Decision In VisitingTourist Areas - Muh Fahrurrozi; Pahrudin; Danang Prio Utomo (JMET: Journal of Management Entrepreneurship and Tourism, 2023)
This study aims to determine the price, location, and facilities jointly affect the decision of tourists in visiting the tourist attraction Park Pusuk Sembalun. This type of research is quantitative research with descriptive correlation method. The sample in this study were 40 samples in the tourist attraction of Puskesmas Sembalun Park in Sembalun Bumbung Village, Sembalun Subdistrict. Methods of data collection using observation, interviews, documentation and questionnaires. Data analysis techniques used are test instruments (validity and reliability), multiple linear regression analysis, classical assumption tests and hypothesis testing. From the results of simultaneous testing shows the variables of factors that influence the visiting of tourists (price, location and facilities) together have a significant influence on the decision of tourists in visiting the tourist attraction park pusuk sembalun. This is evidenced by the acquisition of a calculated F value of 10.345 with a significant level of 0,000 while the degree of freedom value is 3 and 36, so that in F table the value is 2.87. Thus the F value counts 10.345 ˃ F table value (significant). While the partial testing of the price variable has an influence on tourist visiting decisions as much as 0.493 with a t-count of 0.05 and a significant level of 0.002. while location variables and facilities do not have a significant effect. This is evidenced by the value of the location variable of 0.143 with a t-count of 0.05 and a significant level of 0.357 and a variable value of 0.242 with a t-count of 0.05 and a significant level of 0.067.